Mengoptimalkan Kepemimpinan Gembala Dengan Kualitas Pelayanan Gereja - Pinem, Sonny; Nugroho, Andreas; Sianipar, Rikardo (JURNAL KADESI, 2025)
The church has a vital role in guilding and serving the congregation, and its success is greatly influenced by the quality of the pastor’s leadership and the service provided. This study explores strategies to optimize pastoral leadership and improve the quality of church service through a quantitative approach. Data were collected through a survey of a sample of congregations. The results of the regression analysis indicate that transformational pastoral leadership significantly affects the quality of church service. This finding emphasizes the importance of developing pastoral leadership that focuses on service and effective communication. This study contributes to the understanding of the dynamics of leadership and service in the church context.